2016
DOI: 10.1016/j.scitotenv.2016.02.181
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient status of UK groundwater: Nitrogen, phosphorus and organic carbon

Abstract: Groundwater is a large, slowly changing pool of the macronutrients nitrogen (N), phosphorus (P) and dissolved organic carbon (DOC), with impacts on receptors, surface waters, dependent wetlands and coastal marine ecosystems. Sources of N to groundwater include fertilisers, animal wastes and septic led to the reduction observed in rapidly-responding aquifers. For the Chalk, where the unsaturated zone is thick, improvements may not be seen for decades. P is less well-characterised in UK groundwater reflecting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 112 publications
(124 reference statements)
0
19
0
Order By: Relevance
“…Besides, phosphorus (P), which is strongly enriched in many agriculturally used soils due to intensive fertilization (Sch€ arer et al, 2007), also provokes severe environmental problems, especially by facilitating the eutrophication of surface waters. However, losses and pathways of P are still notably poorly understood (Jensen, Olsen, Hansen, & Magid, 2000;Stuart & Lapworth, 2016). The same is true for losses of potassium (K), the third most intensively applied nutrient (Kayser & Isselstein, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, phosphorus (P), which is strongly enriched in many agriculturally used soils due to intensive fertilization (Sch€ arer et al, 2007), also provokes severe environmental problems, especially by facilitating the eutrophication of surface waters. However, losses and pathways of P are still notably poorly understood (Jensen, Olsen, Hansen, & Magid, 2000;Stuart & Lapworth, 2016). The same is true for losses of potassium (K), the third most intensively applied nutrient (Kayser & Isselstein, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile P is particularly problematic as it can be translocated by surface discharge and base flow as well as in drainage water from grasslands to adjacent habitats leading to eutrophication, especially of surface waters (Haygarth et al, 1998;McDowell, Biggs, Sharpley, & Nguyen, 2004;Preedy, McTiernan, Matthews, Heathwaite, & Haygarth, 2001;Stamm, Fl€ uhler, G€ achter, Leuenberger, & Wunderli, 1998). Today, leaching of P is also getting into the focus of ground water quality (Stuart & Lapworth, 2016), for example, caused by increased stocking densities (Jensen et al, 2000). However, in our study, P was not significantly related to grazing intensity, potentially as we pooled different types of livestock (sheep, cattle, horses) for the analyses.…”
mentioning
confidence: 99%
“…Despite site specific observations of high groundwater DOC associated with older aquifers 40 , the model suggests sedimentary OM in young aquifers is more likely to be mobilized than in older, lithified aquifers. Other studies have also reported higher groundwater DOC concentrations originating from the matrix of younger aquifers 41,42 .…”
Section: Resultsmentioning
confidence: 85%
“…We assume that all the C load which reaches the river comes through surface or near‐surface runoff. DOC which leaches through deeper soil layers is partly stored in the subsoil and partly reaches local aquifers, but DOC concentration in UK groundwater is found to be generally less than 1.5 mg L −1 , and lowest in Chalk aquifers [ Stuart and Lapworth , ]. Moreover, DOC is nonconservative, as it is consumed by microbiological processes and the travel time through the Thames aquifer has been estimated to be of the order of 30 years [ Howden et al , ].…”
Section: Discussionmentioning
confidence: 99%